COMPARATIVE STUDY OF TASTE SENSITIVITY TO PHENYLTHIOCARBAMIDE IN NORMOGLYCAEMICS AND IN DIABETES MELLITUS TYPE 2 - DR.MOMI BARUAH; DR.ANJALI JOSHI (International Journal of Pharma and Bio Sciences, 2013)
Taste drives appetite and protects us from poisons.Taste is a sensory cue which is modified by a variety of physiological and pathological factors ranging from genetic, cultural ,aging and hormonal factorsThis study was done to find out the distribution of tasters and non-tasters in normoglycaemics and those with diabetes Mellitus Type 2 and also find out the predisposition to Diabetes in PTC tasters and non- tasters.100 Diabetic and 100 non-diabetic subjects were tested for their taste sensitivity to PTC.